2017
DOI: 10.5116/ijme.595b.b38c
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study of quality of care training and knowledge in Sub-Saharan African medical schools

Abstract: ObjectivesTo identify the level of knowledge and competencies related to quality of care during medical education in sub-Saharan African medical schools.  MethodsA cross-sectional study design was utilized to examine the capacity of medical schools in sub-Saharan African (SSA) countries to teach about the concepts of quality of care and the inclusion of these concepts in their curriculum. A purposeful convenience sampling technique was used to select participants from 25 medical schools in 5 sub-Saharan Africa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…The present study suggests that each university and its affiliated training hospital may have different infection prevention and control curricular content. Different curricula mean different teaching approaches and different clinical experience, which may effect students' perceptions (Bowser et al, 2017). Furthermore, the BSN programs of the 6 universities have varying amount of time for clinical experience of the students.…”
Section: Discussionmentioning
confidence: 99%
“…The present study suggests that each university and its affiliated training hospital may have different infection prevention and control curricular content. Different curricula mean different teaching approaches and different clinical experience, which may effect students' perceptions (Bowser et al, 2017). Furthermore, the BSN programs of the 6 universities have varying amount of time for clinical experience of the students.…”
Section: Discussionmentioning
confidence: 99%
“…Initial development of the questionnaire included literature review for general survey development, themes of the survey and eight previously used questions for measurement of attitudes toward refugees. 7 - 16 , 20 , 21 Two content-area experts assessed the questionnaire for content validity, relevance, and comprehensiveness. The questions were evaluated by Ugandan English speakers to assess for clarity and any need for back-translation.…”
Section: Methodsmentioning
confidence: 99%
“…Many host countries have significantly different healthcare infrastructure and medical education from resettlement countries. 16 - 17 In SSA, both attitudes and educational needs may be different from those in the resettlement countries. To our knowledge, only one study in the field of trauma-informed care by McDonald and colleagues has reported on provider perspectives in host countries.…”
Section: Introductionmentioning
confidence: 99%
“…Students face issues of inadequate housing, transportation, and classroom space . Furthermore, existing programmes often do not emphasise the importance of quality of care in their curricula .…”
Section: Introductionmentioning
confidence: 99%